DISSOLUTION RATES OF PURE METHANE HYDRATE AND CARBON-DIOXIDE HYDRATE IN UNDERSATURATED SEAWATER AT 1000-M DEPTH - Rehder G.; Peltzer E.T.; Kirby S.H.; Stern L.A.; Pinkston J.; Durham W.B.; Brewer P.G. (My University, 2004)
To help constrain models involving the chemical stability and lifetime of gas clathrate hydrates exposed at the seafloor, dissolution rates of pure methane and carbon-dioxide hydrates were measured directly on the seafloor within the nominal pressure-temperature (P/T) range of the gas hydrate stability zone. Other natural boundary conditions included variable flow velocity and undersaturation of seawater with respect to the hydrate-forming species. Four cylindrical test specimens of pure, polycrystalline CH4 and CO2 hydrate were grown and fully compacted in the laboratory, then transferred by pressure vessel to the seafloor (1028 m depth), exposed to the deep ocean environment, and monitored for 27 hours using time-lapse and HDTV cameras. Video analysis showed diameter reductions at rates between 0.94 and 1.20 μm/s and between 9.0 and 10.6 · 10−2 μm/s for the CO2 and CH4 hydrates, respectively, corresponding to dissolution rates of 4.15 ± 0.5 mmol CO2/m2s and 0.37 ± 0.03 mmol CH4/m2s. The ratio of the dissolution rates fits a diffusive boundary layer model that incorporates relative gas solubilities appropriate to the field site, which implies that the kinetics of the dissolution of both hydrates is diffusion-controlled. The observed dissolution of several mm (CH4) or tens of mm (CO2) of hydrate from the sample surfaces per day has major implications for estimating the longevity of natural gas hydrate outcrops as well as for the possible roles of CO2 hydrates in marine carbon sequestration strategies.